Metabolic parameters in cord blood of neonate of mothers with obese and non-obese PCOS and controls: retrospective cohort study - Sanaz Alizadeh; Shahideh Jahanian Sadatmahalleh; Fatemeh Razavinia; Mahnaz Bahri Khomami; Malihe Nasiri; Ashraf Moini; Saeideh Ziaei (BMC, 2021)
Abstract Background Polycystic ovary syndrome (PCOS) is characterized by reproductive disorder and increased risk of metabolic syndrome. This study aimed to assess the metabolic parameters in the cord blood of neonate of mothers with obese PCOS and comparison with non-obese PCOS and controls. Methods This retrospective cohort study was conducted in Arash and Kamali Hospital in 2017-2018. The biochemical test was conducted on 78 neonates from obese PCOS mothers, 78 neonates from non-obese PCOS mothers, and 78 neonates from healthy mothers. Finally, cord blood lipid profile and insulin and blood sugar were determined by specific kits. Correlations between variables were compared with chi-square, Mann-Whitney's U, Kruskal-Wallis H tests and regression model by SPSS 23 and P < 0.05 was considered significant. Results Triglycerides (TG) and high-density lipoprotein cholesterol (HDL) were higher in cord blood of newborn of obese PCOS women than non-obese PCOS and controls (P = 0.02, P < 0.001, respectively). Also, the mean insulin was higher in cord blood of neonate of non-obese PCOS women than in obese PCOS and controls (12.26 ± 12.79 vs. 11.11 ± 16.51 vs. 6.21 ± 10.66, P = 0.01). But in the study, there was no significant difference between the mean of umbilical cord low-density lipoprotein cholesterol (LDL), total cholesterol and blood sugar in three groups. The logistic regression model showed that metabolic parameters were related to PCOS. Conclusions In the present study, there was a significant difference between the mean of umbilical cord HDL, cholesterol, and the insulin level in the three groups. But, there was no significant association between the mean of blood sugar, LDL, and TG in the groups. The metabolic disorder in PCOS might affect cord blood lipid and insulin and adulthood health.